SOCIAL EXCLUSION AND MARGINALISATION OF HOMELESS PEOPLE: A CLARION SOCIAL WORK CALL FOR THE SPIRIT OF UBUNTU TO REIGN - Mahlangu, Timson; Kgadima, Nathaniel Phuti (Social Work/Maatskaplike Werk, 2021)
Social work is committed to the advancement of human rights and social justice. One strategy for promoting social justice is to inculcate a human rights-based approach to social work practice. Using ubuntu as a theorical framework, this article initially explores social exclusion and the accompanying stigma that homeless people experience; it then examines how social workers could apply the principles of ubuntu to re-inscribe homeless people’s human rights. A qualitative study was undertaken with 14 participants who were purposively selected and also identified through snowball sampling. Data were gathered through semi-structured interviews and analysed thematically. Principles of credibility, transferability, dependability and conformability were judiciously adhered to in the research process. The findings indicate that homeless people are the most marginalised population of the community and they are exploited in a variety of ways.